2011
DOI: 10.1186/2045-5380-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potential studies of post-traumatic stress disorder: a critical review and synthesis

Abstract: Despite the sparseness of the currently available data, there is accumulating evidence of information processing impairment in post-traumatic stress disorder (PTSD). Studies of event-related potentials (ERPs) are the main tool in real time examination of information processing. In this paper, we sought to critically review the ERP evidence of information processing abnormalities in patients with PTSD. We also examined the evidence supporting the existence of a relationship between ERP abnormalities and symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 60 publications
6
53
1
Order By: Relevance
“…It is tempting to hypothesize that such overgeneralization may underlie attentional deficits often reported in PTSD patients, as even "insignificant" stimuli ( i.e., neutral stimuli) affect cortical response, thus also affecting the processing of subsequent stimuli. This view is consistent with the P500, suggested to be involved in updating working memory representations (Javanbakht et al, 2011), reported to be impaired in patients with PTSD .…”
Section: Discussionsupporting
confidence: 89%
“…It is tempting to hypothesize that such overgeneralization may underlie attentional deficits often reported in PTSD patients, as even "insignificant" stimuli ( i.e., neutral stimuli) affect cortical response, thus also affecting the processing of subsequent stimuli. This view is consistent with the P500, suggested to be involved in updating working memory representations (Javanbakht et al, 2011), reported to be impaired in patients with PTSD .…”
Section: Discussionsupporting
confidence: 89%
“…Heart rates can be measured through various means including pulse oximetry. Electroencephalography (EEG) event-related potential (ERP) studies of conditioning and extinction in healthy humans and PTSD have been reviewed elsewhere (Javanbakht, Liberzon, Amirsadri, Gjini, & Boutros, 2011; Pitman et al, 2012), and will not be discussed here.…”
Section: 1 Fear Conditioning and Extinction In Healthy Humansmentioning
confidence: 99%
“…Most of these studies have recorded event-related potentials (ERP) using trauma-eliciting stimuli and shown significant increases in the P300 response (for a review see Javanbakht et al, 2011), although Bae et al (2011) found reduced P300 current-source density in patients with PTSD compared to healthy controls in response to non-threatening auditory stimuli.. These seemingly disparate results are consistent with a meta-analysis of ERP studies in PTSD, which found enhanced responses for trauma-related stimuli and reduced responses for neutral stimuli, particularly in the parietal cortex (Karl et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%